Legal requests and instructions in intelligent systems for the field of physical culture and sport - Kolyada, D.M.; Belykh, S.I.; Oleynik, O.S.; Idrisova, N.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to provide specific methods and examples for creating effective legally oriented prompts for the field of physical culture and sport. Methods and structure of the study. The work employs a theoretical analysis of scientific publications based on the ideas of prompt engineering as an educational technology, representing the process of the targeted construction of textual query-prompts ('prompts'). Results and conclusions. Key methodological techniques are presented which allow the prompt-engineering processes of both sports legal specialists and current coaches to be optimised more rapidly. Among them are techniques whereby unnecessary context that distracts from the main goal must be avoided in the query. The prompt should be reformulated so that it sounds universal and meaningful. The key details necessary for an understanding of the question must be enumerated, and so on.